RESEARCH OF INNOVATIVE POTENTIAL OF THE REGION - Kolmykova, Tatiana Sergeevna; Emelyanov, Sergey Gennadievich; Merzlyakova, Ekatarina Aleksandrovna (Journal of Applied Engineering Science, 2017)
Reference points of innovative development of Russian economy are particularly relevant, outlined in the Concept of Long-Term Social and Economic Development of the Russian Federation in modern conditions. However the regional dimension should be taken into account in the formation of an effective national system due to the territorial characteristics and federal structure. From the perspective of the authors, assessment of innovative potential is the most important procedure in the management of innovative development of the economy of the region. Identification of strengths and weaknesses in resource supply of area allows you to define the priorities of innovative development and justify the use of specific instruments of innovation policy in the region. In this paper we propose author’s method of assessment of the region’s innovation potential, based on mathematical and statistical tools. Were made the comparative analysis of the innovation potential of the regions of Central Federal District, and analysis of the structure of the regional innovative potential of the Kursk region. The dynamics of the innovation potential of the Central Federal District of subjects for 2005-2015 were considered. Possible measures to enhance the innovative capacity of the region in view of its structural features were defined.